2022
DOI: 10.3390/brainsci12060775
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Bioeffects in Senescent Mice and Alzheimer’s Mouse Models

Abstract: Ultrasound is routinely used for a wide range of diagnostic imaging applications. However, given that ultrasound can operate over a wide range of parameters that can all be modulated, its applicability extends far beyond the bioimaging field. In fact, the modality has emerged as a hybrid technology that effectively assists drug delivery by transiently opening the blood–brain barrier (BBB) when combined with intravenously injected microbubbles, and facilitates neuromodulation. Studies in aged mice contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…[72] Additionally, there is evidence that UTMD/UTND facilitates the temporary increase of blood-brain barrier (BBB) permeability to enhance drug delivery to the brain parenchyma, so that it is possible to perform immunotherapy for cerebral diseases, particularly glioblastoma, as the most fatal brain cancer. [73][74][75][76] BBB-regulating nanovesicles (BRN) loaded with adenosine 2A receptor agonists were developed to achieve targeted BBB regulation by releasing 2A receptor agonists in the presence of ultrasonication (0.5 W cm −2 , 3 min), further inducing the tight connection between F-actin and endothelial cells (Figure 2c). Figure 2d,e shown that PD-L1 antibody alone could not efficiently enter the orthotopic glioblastoma, thereby leading to the clinical failure of anti-PD-L1 therapy for glioblastoma.…”
Section: Promoting Icb-induced Immunotherapymentioning
confidence: 99%
“…[72] Additionally, there is evidence that UTMD/UTND facilitates the temporary increase of blood-brain barrier (BBB) permeability to enhance drug delivery to the brain parenchyma, so that it is possible to perform immunotherapy for cerebral diseases, particularly glioblastoma, as the most fatal brain cancer. [73][74][75][76] BBB-regulating nanovesicles (BRN) loaded with adenosine 2A receptor agonists were developed to achieve targeted BBB regulation by releasing 2A receptor agonists in the presence of ultrasonication (0.5 W cm −2 , 3 min), further inducing the tight connection between F-actin and endothelial cells (Figure 2c). Figure 2d,e shown that PD-L1 antibody alone could not efficiently enter the orthotopic glioblastoma, thereby leading to the clinical failure of anti-PD-L1 therapy for glioblastoma.…”
Section: Promoting Icb-induced Immunotherapymentioning
confidence: 99%
“…1 US is capable of transmitting energy with high penetration through biological tissues, making it a widely utilized technology in a diverse range of applications. 2 Recent advancements in nanotechnology have facilitated real-time monitoring and diagnosis of diseases. Notably, the synergistic integration of nanotechnology with ultrasound has garnered significant attention, particularly in the context of ultrasound imaging (USI).…”
Section: Introductionmentioning
confidence: 99%